Feasibility of a Hospital at Home for Management of Acute Severe Ulcerative Colitis: A Retrospective Case Series - Anupama A. Goyal; Jeffrey A. Berinstein; Bishu Shrinivas; Peter D. R. Higgins; Stephanie Taylor (Case Reports in Gastrointestinal Medicine)
The Centers for Medicare and Medicaid’s Acute Hospital Care at Home waiver in 2020 has enabled the management of acute conditions that were traditionally cared for in the hospital to transition to the home setting. To our knowledge, data regarding the management of patients with acute severe ulcerative colitis (ASUC) in hospital at home (HaH) programs has not been reported. We conducted a retrospective review of ASUC patients admitted to our HaH program from our adult hospital, who demonstrated early clinical response but required a comprehensive, closely monitored treatment environment that was provided in the patients’ homes. Patients received daily evaluations by hospitalists, gastroenterologists, and registered nurses with clinical assessments, monitoring of vitals, and therapeutics (e.g., intravenous fluids, corticosteroids, etc.), alongside daily blood monitoring for worsening inflammation. Patient demographics and UC disease characteristics were extracted from electronic health records. Outcomes of interest included emergency department (ED) visit, readmission, and mortality within 30 days of index admission; hospital-acquired conditions (HACs) of interest (delirium, catheter associated infections, and falls) during HaH stay; length of stay (LOS) in traditional hospital vs. HaH phase; and need for escalation back to traditional hospital. Three eligible and consenting ASUC patients were transferred to HaH. Two were female and one male, with a mean age of 59.7 years. The mean LOS in the traditional hospital was 8.7 days (range: 4–18), and 6 days (range: 4–9) in HaH. There were no escalations from HaH back to the traditional hospital. One patient had a 30-day ED visit (33%) with readmission (33%). There were no deaths within 30 days of index admission or documented HACs during HaH stay. Our case series highlights the preliminary feasibility of HaH for the management of ASUC patients, as a promising alternative to prolonged hospital-based care, without compromising patient safety or care quality.